The phenomenon of water fluid flow distribution in hydropower pico-hydro viewed from the number of turbine screw winding - Eswanto, .; Siman, .; Pasaribu, Muhammad Nuh Hudawi; Suherman, .; Ilmi, .; Mohd Adnin, Hamidi (Semarak Ilmu Publishing, 2024)
Water is one of the energy sources that has the potential to contribute to replacing energy from fossil materials. This research focuses on picohydro scale hydropower, namely water-based electricity generation as a turbine driving source. Picohydro-scale hydropower is an important part to implement, because the system is not difficult to implement. The aim of the research is to determine the performance of the pico-hydro renewable power plant in terms of the number of turns of the turbine blade screw. The research method was carried out by direct experimentation from a device that had been made using water fluid which was circulated in a closed cycle in pico-hydro hydropower. In the initial stage of the research, drawing designs were carried out, after validation, the tool manufacturing process was carried out. After completion of the manufacturing process, it continues with the testing and measurement process to obtain the desired data. Measurements start from the water flow produced, turbine shaft rotation, transmission rotation, load and power produced. The test model consists of variations in the number of screw turns, namely 9 turns, 11 turns and 13 turns. The results of this research are from data processing and are contained in the discussion obtained under certain operational conditions and discharges ranging from 2 m3/h to 30 m3/h in driving a screw turbine. However, the results obtained are still different, which can be seen in the trend lines in the graphic illustration. The performance in this research can be described in the highest power results reaching 434 Watts with a rotation of 298 rpm at a flow rate of 30 m3/h on a test model with 11 screw winding. This condition is the best result compared to other test models, which is possible because due to several factors, such as being too heavy for an increasing number of screws, uneven distribution of the water fluid flow that pushes the turbine blades.